Sexual Violence Prevention Strategies in Faith-Based Educational Institutions: A Case Study in Grobogan - Mahbubi, Muhammad; Huda, Ali Anhar SyiÔÇÖbul; Bilqis, Amala (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
Sexual violence in religious-based educational institutions remains a critical issue that threatens students' safety and well-being. Despite the assumption that such schools uphold strong moral values, cases of teacher-student misconduct continue to emerge, often exacerbated by power imbalances, inadequate supervision, and cultural stigmas that prevent victims from reporting abuse. This study aims to investigate the contributing factors to sexual violence in religious schools, assess the effectiveness of existing prevention policies, and propose comprehensive strategies to enhance student protection. The research is guided by three key questions: (1) What factors contribute to sexual violence in religious-based schools? (2) How effective are the current policies in preventing such incidents? (3) What strategies can be implemented to strengthen preventive measures in these institutions? This study employs a qualitative research approach using in-depth interviews, observations, and policy analysis. The research focuses on a case study in Grobogan, Central Java, where a recent incident underscores systemic weaknesses in preventing sexual violence. Findings indicate that lack of awareness about ethical teacher-student boundaries, weak institutional supervision, and social stigma surrounding sexual abuse contribute significantly to the problem. Furthermore, reporting mechanisms are often inaccessible or ineffective, discouraging victims from seeking justice. The study proposes establishing anonymous reporting systems, strengthening ethical training for teachers and students, and integrating religious-based sexual education into school curricula. These recommendations aim to foster a safer learning environment by balancing effective child protection with respect for religious and cultural values. This study provides valuable insights for policymakers, educators, and religious leaders to develop holistic, sustainable approaches to preventing sexual violence in schools.